2000
DOI: 10.1287/ijoc.12.3.164.12639
|View full text |Cite
|
Sign up to set email alerts
|

Reactive GRASP: An Application to a Matrix Decomposition Problem in TDMA Traffic Assignment

Abstract: A greedy randomized adaptive search procedure (GRASP) is a metaheuristic for combinatorial optimization. In this paper, we describe a GRASP for a matrix decomposition problem arising in the context of traffic assignment in communication satellites. We review basic concepts of GRASP: construction and local search algorithms. The local search phase is based on the use of a new type of neighborhood defined by constructive and destructive moves. The implementation of a GRASP for the matrix decomposition problem is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
151
0
16

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(167 citation statements)
references
References 14 publications
0
151
0
16
Order By: Relevance
“…However, we also examined a second, reportedly better, strategy called reactive GRASP, in which the parameter a is selfadjusted according to the quality of the solutions previously obtained. The algorithm that we propose (Algorithm 5) is an evolution of Algorithm 1 which is inspired by the GRASP algorithm of Prais and Ribeiro [23].…”
Section: The Choice Of the A Parameter: Reactive Graspmentioning
confidence: 99%
“…However, we also examined a second, reportedly better, strategy called reactive GRASP, in which the parameter a is selfadjusted according to the quality of the solutions previously obtained. The algorithm that we propose (Algorithm 5) is an evolution of Algorithm 1 which is inspired by the GRASP algorithm of Prais and Ribeiro [23].…”
Section: The Choice Of the A Parameter: Reactive Graspmentioning
confidence: 99%
“…Each element of the initial population is generated by the constructive phase of the GRASP algorithm (Resende and Ribeiro, 2008) in a reactive procedure (Prais and Ribeiro, 2000). It can be observed that only feasible solutions are generated by the constructive procedure.…”
Section: Proposed Approachmentioning
confidence: 99%
“…Several options are possible to solve this problem. In particular, a learning-based strategy termed reactive GRASP has been proposed [21]. In this case, the value of the parameter is chosen in each iteration from a set of discrete values Π = {π 1 , · · · , π m }.…”
Section: Reactive Grasp Vs Hybrid Eamentioning
confidence: 99%
“…Any of the selection mechanisms typically used in EAs can be utilized for this purpose. For example, in [21], a roulette-wheel procedure is proposed. Since we are dealing here with a minimization problem, such a proportional approach would not be possible unless goodness values were appropriately transformed.…”
Section: Reactive Grasp Vs Hybrid Eamentioning
confidence: 99%